Business strategy and firm reorganization under changing market conditions - Vivek Ghosal (Center for Economic Studies and ifo Institute (CESifo), 2009)
This study is framed against the increasingly stringent environmental demands on the pulp and paper industry since the late-1980s to reduce water and air pollution, and the global economic slowdown of the early-1990s. The primary focus of this paper is an observation-based analysis conducted by visiting selected paper mills in Finland, the U.S., Germany and Sweden. I find interesting differences and similarities in the firms' strategies in terms of how they responded to these changes in market conditions. Some of the observed differences lie in their focus on achieving (incremental) cost-efficiency gains from better management of the production processes, inventories, supply-chain, product distribution, and timing of modernization investments, including ICT. The second part of the paper presents evidence on firms' productivity paths, and the heterogeneity in productivity among relatively similar firms. I also present selected evidence of these firms' investments in specific areas and how they affected their productivity. The observation of important intra-industry differences across relatively similar firms lends credence to the insights provided by Denrell, Fang and Winter (2003) and Zott (2003), among others. The findings have implications for the study of organizational behavior and business strategies employed by firms to improve their performance and productivity under changing market conditions. We end with some comments on how to assess innovative activity in traditional industries such as pulp and paper.
Keywords: L00; L11; L20; L23; L25; 330; incremental innovation; ICT investments; modernization investments; competitive advantage; production management; supply-chain management; Papierwirtschaft; Wettbewerbsstrategie; Organisationsverhalten; Innovation; Computergestütztes Verfahren; Lieferanten-Kunden-Beziehung; Finnland; USA; Deutschland; Schweden